Uji aktivitas antibakteri kombinasi ekstrak kulit dan biji Pepaya (Carica papaya L.) terhadap bakteri Staphylococcus aureus dan Escherichia coli - Indra Ginting; Singgar Ni Rudang; Muhammad Andry; Mayang Sari; Muhammad Amin Nasution (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background;; Infectious diseases suffered by many people include Enterobacter infection from E.coli and skin infections due to S. aureus. One of the plants that have antibacterial properties is papaya like seeds and skin. Objekctives; The purpose of this study was to determine the activity of papaya skin and Seed (Carica papaya L.) extracts against S. aureus and E.coli. Method; The study used experimental method. The extraction used was maceration with ethanol 80%, 60% solvent. 40% and 20%. Antibacterial Activity Test using disc diffusion method and phytochemical screening test on papaya skin extract (Carica papaya L). Result; The results of screening tests on papaya skin extract (Carica papaya L) were positive for alkaloids, saponins, tannins, flavonoids and steroids. The results obtained at 60% ethanol showed that the combined extract of papaya skin and seeds (Carica papaya L) on S. aureus with concentrations (20:80) - (80:20) was 11.9 mm - 15.6 mm. In E. coli with a concentration (20:80) - (80:20) of 9.7 mm - 14.9 mm. Conclusion; The conclusions from the results of research on the combination of papaya skin and papaya seeds (Carica papaya L) of various concentrations inhibited S.aureus bacteria more than E.coli bacteria.